Egge Simon Mulder, hoogleraar 1956-1970 - Breytenbach, Andries (Hervormde teologiese studies, 1992)
Egge Simon Mulder, professor from 1956 to 1970 E S Mulder succeeded Berend Gemser as professor in Old Testament Studies in the Faculty of Theology (Sec A) at the University of Pretoria. His approach was historicalcritical and at the same time he was totally committed to the ecclesiastical ministry. He can be characterised as an exponent of so-called Ethical Theology. Although he did not fully integrate his scientific work and his theologising within the scope of the church, he contributed to the present close ties between the Faculty and the Nederduitsch Hervormde Church, as well as to the ethos that there is no dichotomy between reason and faith.